EXTRACTION OF FUKOIDAN CHARACTERIZATION FROM CHOCOLATE ALGAE Sargassum sp - Abdul Qadir Jailani; Doni Ferdiansyah (Journal of Aquaculture Development and Environment, 2019)
Fucoidan were recovered from Sargassum polycystum by single-step extraction with ultrasonic wave pretreatment. Extraction were optimized using central composite design of respon surface method. Ultrasonic wave pretreatment conditions were 80% amplitude, for 15 minute. Alga solution in 0.03 M HCl ratio 1:20 (b/v) at 70-90oC for 3-5 hour were evaluated during this process to establish a condition to maximize the extraction. The aim this research is getting the optimum conditions extraction yield fucoidan Sargassum sp. Result this reseacrh all extraction factors had significant effects on fucoidan yield (p<0,05). The optimum conditions were extracting temperature 81oC, extracting time 4,04 h. Under this condition, the experimental yield of crude fucoidan 7,15±5,58%. Based on the characterization result of fucoidan by fourier transform-infrared spectroscopy, we foundthat fucoidan Sargassum sp.is composed sulfate group.